Enhanced effective spin Hall efficiency contributed by the extrinsic spin Hall effect in Pt1-xTax/CoFeB structures - Xu, Zhan (2024)
High effective spin Hall efficiency and low magnetic damping constant are essential to achieve efficient spin-charge conversion for energy-efficient spintronic devices. We report the measurements of effective spin Hall efficiency and magnetic damping constant of Pt1-x Ta x /CoFeB structures using spin-torque ferromagnetic resonance (ST-FMR) techniques. With the increase of Ta content, the spin Hall efficiency increases and peaks x = 0.15 with the value of θ SH eff = 0.35 , before decreases for further Ta content. This non-monotonic variation is attributed to the interaction between the contribution of the extrinsic skew scattering mechanism and the spin-orbit coupling (SOC). The weakening of the SOC in the Pt1-x Ta x layer leads to a decrease in the effective magnetic damping constant with increasing Ta concentration. High-temperature ST-FMR measurements confirm the influence of the Ta concentration on the spin Hall effect and magnetic damping mechanism. Additionally, the decrease in spin mixing conductance and the increase in spin diffusion length leads to a decrease in the interfacial spin transparency.